2006
DOI: 10.1086/498260
|View full text |Cite
|
Sign up to set email alerts
|

XMM-NewtonObservations of High-Redshift Quasars

Abstract: We report on our XMM-Newton observations of the high-redshift quasars BR 2237À0607 (z ¼ 4:558) and BR 0351À1034 (z ¼ 4:351). We also report on XMM-Newton observations of 19 other z > 4 objects available in the public archive of which 14 were detected. We find that the optical to X-ray spectral index ox is correlated with the luminosity density at 2500 8 but does not show a correlation with redshift, which is consistent with earlier results. Radio-loud quasars are brighter and have flatter X-ray slopes compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 101 publications
(168 reference statements)
7
55
2
Order By: Relevance
“…Remarkably, such a value is very similar to those reported from XMM-Newton observations of all the other obscured Blazars at high z for which, bearing in mind the small number statistics, the measured column densities of the absorbers seem to narrowly cluster around N H ≈ 10 22 cm −2 (e.g. F03; W04; Yuan et al 2005;Grupe et al 2005). N H values 10 22 cm −2 are, however, hard to detect at high redshifts and, hence, a selection effect is likely present.…”
Section: Discussionsupporting
confidence: 86%
“…Remarkably, such a value is very similar to those reported from XMM-Newton observations of all the other obscured Blazars at high z for which, bearing in mind the small number statistics, the measured column densities of the absorbers seem to narrowly cluster around N H ≈ 10 22 cm −2 (e.g. F03; W04; Yuan et al 2005;Grupe et al 2005). N H values 10 22 cm −2 are, however, hard to detect at high redshifts and, hence, a selection effect is likely present.…”
Section: Discussionsupporting
confidence: 86%
“…The 1–10 keV part of the observed spectra of AGN is usually modelled as a simple power law with exponential lower and upper cut‐offs specified by ν min and ν max , respectively, where f (ν) is the flux per unit frequency interval and α(>0) is the energy spectral index. For most quasars, the X‐ray spectral index lies in the range 0.7 < α < 0.9 as shown by Wilkes & Elvis (1987) and also recently by Grupe et al (2006) and Lopez (2006). However, some objects show extreme values like α < 0 or α > 2.…”
Section: Constraints and Assumptionssupporting
confidence: 61%
“…Numerous previous studies have searched for a luminosity and redshift dependence of ox ¼ À0:384 log L X /L UV , the ratio of X-ray to UV/optical flux (e.g., Avni & Tananbaum 1982;Wilkes et al 1994;Yuan et al 1998;Vignali et al 2003a;Strateva et al 2005;Steffen et al 2006;, and À X , the X-ray spectra slope (e.g., Reeves & Turner 2000;Bechtold et al 2003;Dai et al 2004;Risaliti & Elvis 2005;Grupe et al 2006). Most studies have found a correlation between ox and UV luminosity, L UV , while the existence of a correlation between ox and z is still a matter of debate (e.g., Bechtold et al 2003;Vignali et al 2003a;Steffen et al 2006;Just et al 2007;.…”
Section: Introductionmentioning
confidence: 99%